Estimating the Cost of Thalassemia Care across the World: A Thalassemia International Federation Model. (2nd November 2022) - Eleftheriou, Androulla; Antoniou, Eleni; Darbà, Josep; Ascanio, Meritxell; Angastiniotis, Michael; Farmakis, Dimitrios
Abstract: Estimating the cost of thalassemia care is important for the optimization of care planning, resource allocation and the empowerment of patient advocacy. However, available evidence is heterogeneous, reflecting diverse healthcare systems and cost estimation methods. We sought to build a globally applicable cost model for thalassemia care. We followed a three-step approach, including (i) a targeted literature review to identify previous cost-of-illness studies on thalassemia; (ii) a generic model development based on the main determinants of cost in different countries emerged from a literature review and validated by a team of medical experts; (iii) a piloting of the model using data from two diverse countries. The literature review revealed studies focusing on the total costs of thalassemia care or the cost or cost-effectiveness of specific treatment or prevention modalities in high- and low-prevalence countries across the world. The resulting evidence was used to build a model that calculates total annual therapy cost based on entry of country-level and patient-level data, and data on healthcare modalities, indirect costs and prevention. Testing the model using published data from the UK, Iran, India and Malaysia, revealed an annual cost per patient of £81, 796.00 for the UK, Iranian rial (IRR) 13, 757.00 for Iran, Indian rupee (INR) 166, 750.00 for India and Malyasian ringgit (or dollar) (MYR) 111, 372.00 for Malaysia. A globally applicable model that calculates total annual cost of thalassemia care was built based on existing evidence. The model successfully predicted the annual cost of thalassemia care in the UK, Iran, India and Malaysia.